1988
DOI: 10.14430/arctic1730
|View full text |Cite
|
Sign up to set email alerts
|

Holocene Sea Levels in Southeast Alaska: Preliminary Results

Abstract: ABSTRACT. Natural raised marine deposits and archaeological sites recently discovered in southeastern Alaska have been measured relative to mean sea level and radiocarbon dated. Plots of sites on Heceta and Prince of Wales islands are compared to those developed for British Columbia. The Heceta Island curve is comparable to that of the Queen Charlotte Islands, in which pre-Holocene shorelines were lower than present until about 10 O00 B.P. and then rose to a maximum of 15 m as1 by 8500 B.P., when gradual emerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Andrews et al 1971;Cannon 2000;Clark and Fitzhugh 1992;McGhee 1979), as well as in Southeast Alaska (e.g. Giddings and Anderson 1986;Mobley 1988). Also, in the European North, along the coast of northern Norway resembling studies have found a solid ground (e.g.…”
Section: Shore Displacement and Shoreline Determinationmentioning
confidence: 96%
“…Andrews et al 1971;Cannon 2000;Clark and Fitzhugh 1992;McGhee 1979), as well as in Southeast Alaska (e.g. Giddings and Anderson 1986;Mobley 1988). Also, in the European North, along the coast of northern Norway resembling studies have found a solid ground (e.g.…”
Section: Shore Displacement and Shoreline Determinationmentioning
confidence: 96%
“…The shell date provides a minimum age for the ensuing transgression in the Gulf of Esquibel, which rose above the present datum around 10.7 to 10.1 ka BP. A high stand of less than þ16 m amsl at Heceta Island on the northern boundary of the Gulf of Esquibel was reached between 9.5 and 7.6 ka BP (Ackerman et al, 1985;Mobley, 1988;Baichtal and Carlson, 2010), while at Prince of Wales Island on the eastern boundary of the Gulf, RSL reached at least þ14 m amsl by 9.8 to 9.1 ka BP. Following the high stands, the sea regressed, reaching below þ14 m amsl on Heceta Island (Mobley, 1988) and approximately þ1 m amsl at Prince of Wales Island in the mid-Holocene (5.5 to 4.5 ka BP and 5.3 to 4.9 ka BP, respectively) (Fig.…”
Section: Outer Islands-north Coastmentioning
confidence: 99%
“…Elevated terraces and shell‐bearing marine deposits have long been noted in Southeast Alaska (Buddington & Chapin, ; Swanston, , ; Ackerman, , ; Ackerman et al., ). Using these data as well as new information, Mobley () developed Holocene sea‐level curves for Heceta and Prince of Wales Islands based on the ages and elevations of raised shell‐bearing strata and compared them to those of British Columbia (Clague et al., ), as suggested by Rabich‐Campbell (). Clague et al () identified inner‐, middle‐, and outer‐coast paleoshorelines, with a forebulge influencing the middle and outer shoreline elevations.…”
Section: Paleogeography and Sea Level Backgroundmentioning
confidence: 99%